2021
DOI: 10.1002/ldr.4024
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐related response of soil enzymes to cyanobacteria‐dominated crusts along a precipitation gradient

Abstract: This study aimed to elucidate the ecological role of cyanobacteria-dominated crusts on soil enzymes activities along a precipitation gradient. Results showed that proteins and polysaccharides contents of cyanobacterial-dominated crusts changed significantly among nine sample sites. Meanwhile, proteins and polysaccharides displayed a downward trend with increasing thickness and decreased with increasing mean annual temperature, while these two first increased, and then decreased with increasing chlorophyll a. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In this study, different soil enzyme activities were found to vary greatly in different regions and at different soil depths. With the increase in soil depth, the activities of soil URE, SUC, and ALP showed a downward trend, which is consistent with the findings of Zhang's study [40], while the changes in soil CAT activity were not significant (Figure 3). The soil enzyme activities in the coal mining subsidence area were significantly lower than those in the non-subsidence area at some soil layers, which is consistent with the findings of Ma's study on the northwestern arid and semi-arid mining area [41].…”
Section: Effects Of Coal Mining Subsidence On Soil Enzyme Activitysupporting
confidence: 88%
“…In this study, different soil enzyme activities were found to vary greatly in different regions and at different soil depths. With the increase in soil depth, the activities of soil URE, SUC, and ALP showed a downward trend, which is consistent with the findings of Zhang's study [40], while the changes in soil CAT activity were not significant (Figure 3). The soil enzyme activities in the coal mining subsidence area were significantly lower than those in the non-subsidence area at some soil layers, which is consistent with the findings of Ma's study on the northwestern arid and semi-arid mining area [41].…”
Section: Effects Of Coal Mining Subsidence On Soil Enzyme Activitysupporting
confidence: 88%
“…Two grams of fresh soil was mixed with 10 mL of 10% sucrose solution, 2 mM sucrose solution prepared in 10 mM phosphate buffer (pH 5.5) followed by adding a few drops of toluene (Curtright & Tiemann, 2021). The mixture was shaken and incubated at 37°C for 24 h. Next, 3,5‐dinitrosalicylic acid was added to determine sucrose concentration at 508 nm (Cordero et al., 2019; Zhang et al., 2023).…”
Section: Methodsmentioning
confidence: 99%